EFEKTIVITAS BUDAYA LITERASI DALAM MENINGKATKAN MINAT MEMBACA AL-QUR’AN SISWA DI MADRASAH IBTIDAIYAH NEGERI 3 SAMBAS TAHUN PELAJARAN 2022-2023 - AGISTA, MELY (Lunggi Journal, 2024)
This research discusses: 1) Implementation of literacy culture in increasing students' interest in reading the Al-Qur'an at MIN 3 Sambas for the 2022/2023 academic year. The effectiveness of literacy culture in increasing students' interest in reading the Koran at MIN 3 Sambas for the 2022/2023 academic year; 3) Supporting and inhibiting factors in implementing literacy culture in increasing students' interest in reading the Al-Qur'an at MIN 3 Sambas. This research technique uses a qualitative approach with a phenomenological type of research. Data collection techniques use interviews, observation and documentation. The data analysis techniques used are data reduction, data presentation, and data conclusion. The data validity checking technique uses triagulation and member check. The research results show that: The implementation of literacy culture in increasing students' interest in reading at MIN 3 Sambas for the 2022-2023 academic year is divided into three stages, namely the habituation stage, development stage and learning stage. The effectiveness of literacy culture in increasing interest in reading the Al-Qur'an at MIN 3 Sambas is effective according to the measure of effective achievement of a program from comparing the processes and results of literacy culture activities, namely program success, target success and overall achievement. Supporting and inhibiting factors for implementing literacy culture in increasing students' interest in reading the Al-Qur'an at MIN 3 Sambas for the 2022-2023 academic year, namely supporting factors for implementing literacy culture include: the existence of adequate facilities and infrastructure, collaboration between teachers in the literacy culture process as well as support from students' parents, factors inhibiting the implementation of literacy culture include: allocation of literacy time, different student characters, low student interest and students' understanding in reading the Al-Qur'an.